Um olhar sobre a história da organização curricular da educação física no Colégio de Aplicação da Universidade Federal de Sergipe (1959-1996) - Guimarães, Mariza Alves (2016)
This research has the general objective understanding of curricular setting of physical education discipline in the wider curriculum CODAP-UFS; having as a landmark - cut - the time period from 1959 until 1996. Whereas on numerous curriculum theme approaches can be found on the horizon of the investigation, like the sociological, legal, political, economic, educational, pedagogical approaches etc., study the specific curriculum of Physical Education under the "history of the school curriculum" reminds us of the necessary understandings and fields about theoretical and methodological elements that constitute the foundations of historiographical look and inclinations for this research field; that is the education in the wake of their problems. In this sense, the well demarcated object of this work is the curriculum of physical education and its transformations linked to curriculum development CODAP-UFS. Our hypothesis considers the dialectical relationship between both curricular stories, and in this sense we hold two possibilities to observe the way that physical education materialized in the curriculum. The theoretical and methodological foundations of our study can be found in the academic and scientific field of History Curriculum, not losing sight of the history of school subjects, based on the reading of Chervel studies (1990) and Goodson (1995). In addition to concepts such as school culture, from Julia (2001). We use historical research field, such as qualitative approach. We follow the methodological guidance grounded in the new studies of educational historiography, and use historical sources, documents, laws, institutional acts, newspapers, photographs. Also we use oral history to get more elements to the understanding of our object of study for this interview 03 physical education teachers who taught classes in the given period in this study. From the data found can say that Physical Education was present in the curricular organization Application College since its opening, and most of the time was as educational practice in order to contribute to shaping individuals to social life, where rules and discipline must be seized. The teaching staff who taught Physical Education at the UFS Application College was composed of invited teachers, others were affiliated with the course of Physical Education of the UFS, some were provided by the State Department of Education of Sergipe, others came from contest to substitute and effective teacher of own institution. Physical education is seen as a discipline when observing the need for specific teachers and prepared to organize and guide their teaching, knowledgeable individuals from knowledge specific to this area and specific and government agencies to care for your education. As for the knowledge taught in the Physical Education identified gymnastics, sports, knowledge related to health and hygiene. Knowledge taught through practical classes and lectures, often without presenting a continuity as noted in school reports. Regarding the curriculum UFS Application College observed the presence of events, experiences and attitudes that marked the passage of students through physical education. We noticed that there was a dialectical relationship between curriculum of Physical Education and UFS Application College curriculum the study period, given that the teachers interviewed showed no institutional guidance in relation to the curricular organization of physical education taught by them.